Spiritualitas Dalam Akuntansi Sang Pembebas Dari Kuasa Kapitalisme - Ida Ayu Nursanty; Endang Kartini; I Made Murjana (Akuntansi & Ekonomika, 2021)
The objectives of the research are to criticize the modern accounting is entrenched under the auspices of capitalism, especially accounting in Indonesia, and to an alternative idea for a better one. Is done as there as a strength that accounting for capitalism has reached a deadlock in answering current problems. Conventional accounting as a product of the modern era which has the spirit of capitalism is always oriented towards maximizing profit and rationality of recording. The impact of this understanding makes accounting a means of legitimating certain parties to seek maximum profit, without paying attention to other artificial interests. Through a rasionalis spiritualist approach, the research suggests the internalization of "spirituality" which refers to Islamic spirituality. Under the internalization of Islamic spirituality, accounting can be separated from the domination of capitalism.